Fabrication of antimicrobial platinum-graphene/polypropylene Pt-GNPs/PP nanofilter for PMs capturing and high quality air - Amjed R. Qarahgouli; Khalid A. Sukkar; Alaa M. Ali (Results in Materials)
Recently, the development of air filters has been spurred by air pollutants and the global epidemic of infectious illnesses and their effects on human health. Specifically, it has been noted that indoor air pollution rates are rising due to a variety of contaminants and microorganisms. As a result, novel air filters that are easy to use and have cheap production costs have to be produced. In this research have been fabricated new air nanofilters in hybrid performance for high-quality air in particulate matters capturing and antimicrobial activities. The air nanofilter is prepared by the integration of hybrid nanoparticles (Pt-GNPs) into polypropylene (PP) textiles by a coating method. The Pt-GNPs formed from graphene nanoparticles obtained from graphite via the modified Hummers' method and platinum ions from hexachloroplatinic acid. These nanofilters exhibit high particulate matters filtration efficiency reaching 93.16 % and a low pressure drop of 88.25 Pa. In addition, it was found when the GNPs/PP nanofilter was combined with other layers of sponge and cotton as auxiliary filters the efficiency increased to 99.03 %. Furthermore, the results demonstrated the ability of each sample to influence E. coli more than S. aureus, which provided killing activity reached 100 % at 0.6 % Pt-GNPs against all types of microorganisms that have been tested. These filters can easily be used in different applications such as the mask face or in air conditioning systems as well as in air purification devices with high filtration performance and effective cost.